Coblation-Assisted Endoscopic Approach for Airway Stenosis - Vikas Gupta; Kiran Upadhyay; Rakesh Datta; Sheetal Raina; Ritika Bhatia; BR Lohith (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Acquired laryngotracheal stenosis is a challenging condition for the otolaryngologist. The gold standard of treatment for a long time has been open surgical procedure but not without significant morbidities. To avoid morbidities, various endoscopic approaches like balloon dilatation, stenting, CO2 laser, and cryotherapy have emerged in the last decade. Coblation-assisted tracheoplasty is one such novel approach which enables the removal of target tissue with minimal damage to surrounding tissues. Aim and Objectives: The aim of this case series is to evaluate the use of bipolar radiofrequency plasma ablation (Coblation) in the treatment of acquired adult tracheal stenosis. Materials and Methods: This is a retrospective case series in a tertiary care center. The medical records of six patients with tracheal stenosis who were treated with coblation from March 2020 to December 2020 were reviewed. Patient presentation, surgical intervention(s), post-operative course, and complications were analyzed. Result: All six patients had acquired tracheal stenosis post-tracheostomy. Coblation along with balloon dilatation and Mitomycin-C were done for these patients. All six patients could be successfully decannulated without complications, perioperative, or post-operative sequalae. Conclusion: The results of this study suggest that coblation may be an effective endoscopic tool for the treatment of tracheal stenosis. Further studies with a large number of patients are required as this technique comes more in application.